Ten rock-shelter inscriptions from Ruhuna, southern Sri Lanka - Falk, Harry (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The paper presents some hitherto unknown early cave inscriptions from Southern Sri Lanka, together with some published ones which deserved a revision. The texts add new names, professions and titles to the vocabulary of early Sinhalese Prakrit.The article will be available as a PDF in the near future.